2014
DOI: 10.1186/1471-2253-14-64
|View full text |Cite
|
Sign up to set email alerts
|

Lung volume assessments in normal and surfactant depleted lungs: agreement between bedside techniques and CT imaging

Abstract: BackgroundBedside assessment of lung volume in clinical practice is crucial to adapt ventilation strategy. We compared bedside measures of lung volume by helium multiple-breath washout technique (EELVMBW,He) and effective lung volume based on capnodynamics (ELV) to those assessed from spiral chest CT scans (EELVCT) under different PEEP levels in control and surfactant-depleted lungs.MethodsLung volume was assessed in anaesthetized mechanically ventilated rabbits successively by measuring i) ELV by analyzing CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…To optimize EELV NMBW performance, longer stabilization periods would probably have been needed which was not possible due to the aforementioned time constraints..Our previous experimental validation studies found that ELV resulted in larger values than EELV at lower PEEP levels in pigs and rabbits 3,15. Higher levels of PEEP impair lung perfusion and could potentially decrease ELV relative to EELV, but this was not observed in this study, possibly because PEEP was not increased enough to compromise lung perfusion.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…To optimize EELV NMBW performance, longer stabilization periods would probably have been needed which was not possible due to the aforementioned time constraints..Our previous experimental validation studies found that ELV resulted in larger values than EELV at lower PEEP levels in pigs and rabbits 3,15. Higher levels of PEEP impair lung perfusion and could potentially decrease ELV relative to EELV, but this was not observed in this study, possibly because PEEP was not increased enough to compromise lung perfusion.…”
mentioning
confidence: 67%
“…Trending was reliable, although scattered, with a 100% concordance rate between ELV and EELV when PEEP was changed from 0 to 5 cm H 2 O, in line with results from our previous animal experiments. 3,15 Although bias was low, agreement between EELV and ELV was poor, as indicated by wide LoA and high PE.…”
Section: Discussionmentioning
confidence: 99%
“…EELV He was determined by a helium (He) MBWT (EXHALYZER D; ECO Medics AG) procedure that has been validated and described in detail in previous publications 8,10 …”
Section: Methodsmentioning
confidence: 99%
“…The He flow was then interrupted, and the washout dilution of the tracer gas was recorded. EELV He was calculated from the changes in the He concentration during the washout phase by special software, (Spiroware, V1.4.3, ECO Medics AG) as previously described 8,10 . The instrumental dead space between the capnograph and point of EELV He measurement (3.8 mL) was subtracted from the reported EELV He values.…”
Section: Methodsmentioning
confidence: 99%
“…26 This specific pattern of breathing is achieved by an additional software of the Servo-i ventilator that creates 5 consecutive alterations in inspiratory/expiratory ratio (1:2 to 1.5:1) by varying the inspiratory pause. 27 Airflow and expired CO 2 are measured by the ordinary Y-piece flow sensor and a main stream CO 2 transducer. Flow and CO 2 data from Servo-i are exported, via the RS232 port, to a laptop with a special designed software application written in Matlab (Mathworks, Natick, MA).…”
Section: Measurement Of Effective Lung Volume and Pbfmentioning
confidence: 99%